The Performance of Procurement Functions in Public Universities in Kenya: Assessing the Potential Influence of Supplier Development - Musyoka, Festus Muema; Namusonge, Gregory Simiyu; Musau, Enock Gideon (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study investigates the influence of supplier development initiatives on the performance of procurement functions in public universities in Kenya, focusing on critical dimensions such as process integration, strategic collaboration, supplier capability enhancement, and innovation. Methodology: The study adopted a post-positivist epistemology and employed a causal-comparative design. Data were collected using structured questionnaires from 93 procurement professionals across various Kenyan public universities. Findings: The results revealed that supplier development accounted for 30.8% of the variance in procurement function performance, affirming its moderate but statistically significant explanatory power. Specifically, process integration and supplier capability enhancement emerged as significant predictors of procurement efficiency, aligning with prior findings that emphasize the role of strategic supplier partnerships in institutional procurement. Unique Contribution to Theory, Policy and Practice: Contextualized within the evolving Kenyan higher education landscape—marked by a new funding model requiring cost transparency and fiscal accountability. This research highlights the urgent need for public universities to institutionalize continuous supplier engagement, implement supplier innovation programs, and cultivate mutually beneficial partnerships. These strategies are essential not only for improving procurement performance but also for ensuring institutional sustainability and compliance with public accountability requirements.